APPLICATION OF EXCITATION EMISSION MATRIXES SPECTROSCOPY TO STUDY HUMIC ACIDS REJECTION WITH TiO2 NANOFILTRATION MEMBRANE WITH ENLARGED AREA - MIHAELA-ELENA DASCĂLU; JUAN ANTONIO LÓPEZ-RAMÍREZ; VALENTIN NEDEFF; EMILIAN MOSNEGUȚU; DRAGOS RUSU (Scientific Study & Research: Chemistry & Chemical Engineering, Biotechnology, Food Industry)
In recent years, membrane technology is increasingly being studied and thus became even more used in the production of drinking water. However, the presence of foulants in natural waters, as humic acids, affects strongly the efficiency of membrane processes. This study has been aimed to study humic acid (HA) rejection using a new TiO2 ceramic nanofiltration membrane, with enlarged area (1.25 sqm). This membrane is a prototype and it has been chemically modified to increase its resistance to get fouled. The experiments were carried out on a pilot scale, in the laboratory within the Department of Environment ‧Technologies, from the University of Cádiz, Spain. For this, ultrapure water and different HA concentrations (10 mg‧L-1, 25 mg‧L-1, 50mg‧L-1, 75mg‧L-1, 100 mg‧L-1) were used. For the operating conditions, a constant temperature of 20 °C, pH 7.0, a constant pressure of 7 bars and a Cross Flow Velocity of 0.7 m‧s-1 were used. The analytical measurements focused on the use of excitation-emission fluorescence matrix to study membrane rejection of HA. The results of the conducted experiments show that this instrumental technique helps to control the rejection of HA in water and, at the same time, highlights the potential of the prototype membrane for controlling organic matter from the water.